Penghapusan diskriminasi, ras, dan etnis pembuatan surat keterangan waris yang didasarkan pada penggolongan penduduk - Fadilla Dwi Lailawati (University of Merdeka Malang, 2020)
Inheritance law is inseparable from the origin of the Indonesian nation which consists of various ethnic or ethnic groups so there are various rules that have been formed related to inheritance law in Indonesia. Population classification and the applicable law for each of these groups are based on the provisions of 163 paragraph (1) IS (Indische staats Regeling 2 inherited from the Dutch East Indies Colonial Government. Supervising the population in the colony and politics of duping for the population in the Dutch East Indies at that time the Indonesia population groups, namely the European Group the Indigenous Group, and the foreign eastern group.How to cite item: Lailawati, F. (2020). Penghapusan diskriminasi, ras, dan etnis pembuatan surat keterangan waris yang didasarkan pada penggolongan penduduk. Jurnal Cakrawala Hukum, 11(1), 12-20. doi:https://doi.org/10.26905/idjch.v11i1.4051